A resume of maximum lift data for symmetrical wings, with various high-lift aids - Nonweiler, T. (College of Aeronautics, 1954)
We shall attempt here to summarise the existing data on the values of the low-speed CLmax of wings, in the absence of a fuselage, and without including information on stalling incidence or pitching moment. The summary is limited to the consideration of unswept wings, and those of delta planforms, which have symmetrical sections: there is some discussion of the maximum lift increments due to the use of flaps of various kinds.